Current Parents and Children’s Leisure Time - Mendelová, Eleonóra; Gužíková, Libuša (Journal of Vasyl Stefanyk Precarpathian National University, 2023)
This paper presents research focused on investigating contemporary parents and selected aspects of their influence on children's leisure time, emphasizing how and to what extent parents organize their children's leisure time. Parents from different regions of Slovakia participated in the research, and we processed the results using descriptive statistics. For comparison, we used the Student T-test, Mann-Whitney Test (for comparing two groups), and Kruskal-Wallis Test (for comparing three or more groups). The research showed that respondents judge current parenting as different and significantly more challenging compared to the past. They perceive differences in the sphere of leisure time of families, especially in the fact that parents give fewer responsibilities to children than the previous generation of parents. The research also shows that the problem of contemporary families is the absence of time spent together by parents and children, the absence of family communication, and the high level of organization of children's leisure time by parents. The authors point out that parents in a postmodern society have to deal with the difficulties of ensuring the family's economic stability, which is why two-career marriages are a reality in contemporary families. It has been proven that today's parents are busier with work and are more engaged outside the family, as a result of which they spend less time with their children, which negatively affects their upbringing, there is a lack of quality family communication, and children feel lonely and deprived of parental attention. It was also found that in the modern family, students are involved in housework much less than in the past, so they mostly have no experience of work in this aspect. It is emphasized that the compensation of parental influence with other means of education - media, technology (smartphones, tablets, computers), and the virtual world (social networks) is alarming. The decline in the development of reading interests in the family is outlined, and the tendency of parents to replace the joint reading of children's books with modern technologies is revealed.